2010
DOI: 10.5424/fs/2010193-9082
|View full text |Cite
|
Sign up to set email alerts
|

Biomass allometry and carbon factors for a Mediterranean pine (Pinus pinea L.) in Portugal

Abstract: Forests play an important role in the global carbon balance because they offset a large portion of the carbon dioxide emitted through human activities. Accurate estimates are necessary for national reporting of greenhouse gas inventories, carbon credit trading and forest carbon management but in Portugal reliable and accessible forest carbon measurement methodologies are still lacking for some species. The objective of this study was to provide forest managers with a comprehensive database of carbon factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
34
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 43 publications
16
34
2
5
Order By: Relevance
“…An opposite trend was shown by Correia et al, (2010). Our results seem in accordance with some authors findings (e.g.…”
Section: Correlation Between Bcef Dbh H Sp and Pdsupporting
confidence: 83%
“…An opposite trend was shown by Correia et al, (2010). Our results seem in accordance with some authors findings (e.g.…”
Section: Correlation Between Bcef Dbh H Sp and Pdsupporting
confidence: 83%
“…This finding is consistent with other studies that have documented significant variation between sapwood, heartwood, and bark within conifers [27,28,31,38]. In a review of existing carbon fraction studies, Thomas and Martin [29] found only six studies that measured carbon fractions for different bole tree tissues and none of those studies looked at carbon fractions as measured by all of the common methodologies.…”
Section: Carbon Fraction Modelingsupporting
confidence: 77%
“…Density and carbon fraction of tree bark are not well-studied, although bark can be a significant portion of total tree biomass and can have a higher carbon fraction than stemwood [31,38]. This difference in carbon fraction between bark and stemwood suggests that bark carbon fraction should be measured directly and not assumed to be the same as the stemwood.…”
Section: Introductionmentioning
confidence: 99%
“…BEFscrown had higher values in thinner plots, whereas BEFsstem were higher in denser stands. As reported by other authors (Correia et al 2010) BEFscrown decreased with increasing density, and BEFsstem increased with increasing density. Generally, BEF values are high at low stand growing stem volumes or biomass, and decrease to a constant BEF at a high stand growing stem biomass.…”
Section: Age-dependent Befssupporting
confidence: 68%
“…When selecting or developing BEF values, care should be taken that they are representative of the forest population to which they will be applied, with respect to the species and according to tree size. The relative share of biomass components (e.g., foliage and branches) varies during stand development, according to age (Lehtonen et al 2004), fertility (Wirth et al 2004) and stand density (Correia et al 2010). …”
Section: Age-dependent Befsmentioning
confidence: 99%